Advancing Governance Innovation in Zakat Institutions: A Good Corporate Governance Model for Improving Compliance and Social Impact at LAZISMU, Indonesia - Khoirul Umam; Mulyono Jamal; Khurun'in Zahro'; Nabilla Rahmani (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Zakat has great potential if managed professionally. However, there are still many zakat institutions that have not been optimal in their management, so that good governance is needed, one of which is the principle of Good Corporate Governance (GCG). The purpose of this research is to find out how the management of zakat funds in the Amil Zakat Muhammadiyah Yogyakarta Special Region (LAZISMU DIY) in Indonesia is based on GCG principles. This research uses a descriptive qualitative method to deepen understanding of the practice of applying the principles of Good Corporate Governance (GCG) in the management of zakat funds at LAZISMU DIY. In collecting data, researchers used the triangulation method and analysed it using the inductive-deductive method to analyse the extent to which the management of zakat funds in LAZISMU DIY is based on GCG principles. The results of this study indicate that the management of zakat funds in LAZISMU DIY has been in accordance with sharia provisions and GCG principles. This is evidenced by the publication of activities and financial reports of the institution in the mass media (transparency); pay attention to the interests of all stakeholders (accountability); comply with applicable regulations (responsibility); no interference from other institutions and fairness (independence); refers to fair treatment of all company stakeholders (justice). Thus, the management of zakat funds in LAZISMU DIY has been in accordance with GCG principles and provides benefits to the community, especially mustahik. Researchers suggest that zakat institutions synergise more to increase public awareness of giving zakat.